2022
DOI: 10.1186/s12959-022-00416-9
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation control, outcomes, and associated factors in long-term-care patients receiving warfarin in Africa: a systematic review

Abstract: Background Oral anticoagulation therapy with warfarin requires frequent monitoring level of anticoagulation by the international normalized ratio (INR). In Africa, studies that explore anticoagulation control, treatment outcomes, and associated factors are reported in various ways in long-term patients receiving warfarin therapy to generate concrete scientific evidence. Methods The literature search was conducted in PubMed, Cochrane Library, Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
3
1
1
Order By: Relevance
“…This approach has been increasingly recognized for its capacity to provide personalized patient education, ensure consistent monitoring, and facilitate precise dosage adjustments, including the management of complex therapies, such as warfarin [ 61 ]. The difference between the outcomes of this study and the typical lower TTRs reported in African countries [ 32 ] further emphasizes the unique impact of PLAS in resource-limited settings. This finding suggests that PLAS may expand beyond high-income countries and offer a viable solution for improving anticoagulation management.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…This approach has been increasingly recognized for its capacity to provide personalized patient education, ensure consistent monitoring, and facilitate precise dosage adjustments, including the management of complex therapies, such as warfarin [ 61 ]. The difference between the outcomes of this study and the typical lower TTRs reported in African countries [ 32 ] further emphasizes the unique impact of PLAS in resource-limited settings. This finding suggests that PLAS may expand beyond high-income countries and offer a viable solution for improving anticoagulation management.…”
Section: Discussioncontrasting
confidence: 72%
“…Most patients in both groups were female, with no significant differences ( p = 0.31) between the groups in each sex category. The median (IQR) age in the UMC was 41.00 [ 32 55 ] years, with a range of 18–82 years, while in the PLAC group, the median ± IQR of age was 39.00 [ 32 49 ] years, with a range of 20–85 years without any significant difference between the groups ( p = 0.15). A significant difference was observed based on the residence of the patients, and the majority of patients were residents of Addis Ababa (study area) in both the UMC and PLAC: 247 (70.6) and 148 (84.6), respectively ( p < 0.001) (Table 1 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… 71 While mechanical valve replacement does offer benefits in terms of longevity, it is important to note that anticoagulation management is challenging in LMICs, leading to higher rates of valve thrombosis, thromboembolism, and bleeding complications than in industrialized nations. 72 Surgical options for rheumatic mitral valve disease are summarized in Figure 4 .
Figure 4 Operative Interventions for RHD .
…”
Section: Rheumatic Mitral Valve Interventionsmentioning
confidence: 99%
“…geral foram de 65 ± 20% e 68% (IQR 53-79%) e na África do Sul (58,1% ± 16%). Considerados assim, bons resultados quando comparados a outros países em desenvolvimento(TADESSE et. al., 2022).…”
unclassified